2021
DOI: 10.3168/jds.2020-18896
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity influences social networks in dairy cows after regrouping

Abstract: Regrouping is common practice when managing dairy cow groups, and it is known to have disruptive effects on behavior and production. The presence of a small group of familiar cows upon regrouping may provide social support and mitigate some of the negative effects. In this study we investigated (1) how regrouping affects social relationships among familiar cows and (2) if cows prefer familiar individuals over unfamiliar ones as social partners after regrouping. We used 3 established groups of cows to create 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
(60 reference statements)
1
13
0
Order By: Relevance
“…Affiliative interactions between kids of different treatments were less frequent than affiliative interactions between kids of the same treatments after weaning, but across weeks, kids play-fought and lay in contact with kids from the other rearing treatment more often, suggesting they had become familiar with each other and affiliative relationships may have developed even between treatments. This is in line with previous studies in cattle, showing that preferential social relationships remain after mixing and take time to form between former unknown peers (Foris & Haas, 2021;Gutmann et al, 2015;Gygax et al, 2010;Nowak & Boivin, 2015;Rocha et al, 2020).…”
Section: After Weaningsupporting
confidence: 93%
“…Affiliative interactions between kids of different treatments were less frequent than affiliative interactions between kids of the same treatments after weaning, but across weeks, kids play-fought and lay in contact with kids from the other rearing treatment more often, suggesting they had become familiar with each other and affiliative relationships may have developed even between treatments. This is in line with previous studies in cattle, showing that preferential social relationships remain after mixing and take time to form between former unknown peers (Foris & Haas, 2021;Gutmann et al, 2015;Gygax et al, 2010;Nowak & Boivin, 2015;Rocha et al, 2020).…”
Section: After Weaningsupporting
confidence: 93%
“…This suggests that the 24h patterns of primiparous cows were revealing more eating time and longer walking time patterns as the quantified effect of hierarchical differences between primiparous and multiparous cows. Primiparous cows also have less weight than older animals which might result in evasive behavior when conflicts for feed, milking order or resting places arise especially after introduction to the milking herd for the first time [58][59][60]. Combining these effects on behavior, health, production and growth, it could be advisable to house primiparous cows separate from multiparous cows, which is relatively simple to implement in larger herds [61].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has reported that, when housed in a freestall barn, the majority of agonistic interactions take place in the feeding area 18 , 29 (i.e., feed bunk). Although displacements also occur in other areas of the pen 30 , 31 , feed related competition has been validated to be a practical proxy to measure dominance in captive dairy cow groups 32 . To avoid receiving aggressive interactions, subordinate cows can use a variety of strategies, including feeding at less competitive times 19 , 33 .…”
Section: Introductionmentioning
confidence: 99%